Manufacturing method of silicon carbide nanowire enhanced gallium indium liquid metal composite graphene oxide ultralight electromagnetic absorption aerogel

By optimizing the composite process of silicon carbide nanowires, gallium indium liquid metal and graphene oxide, low-density and high-performance electromagnetic absorption aerogels are prepared, which solves the problem of poor material synergy in the existing technology and achieves widespread application in aerospace, electronic equipment and other fields.

CN120248411APending Publication Date: 2025-07-04HARBIN INST OF TECH AT WEIHAI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510276029.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The prior art is difficult to combine the ultralight electromagnetic absorption aerogels prepared by composite silicon carbide nanowires, gallium indium liquid metals and graphene oxide. The advantages of the materials are not fully combined, resulting in poor synergy effects and cannot meet the needs of aerospace, miniaturization of electronic equipment, and military stealth.

Method used

Through the rational design of the material composition and preparation process, silicon carbide nanowires, gallium indium liquid metal, sodium alginate, polyvinyl alcohol, sodium carboxymethylcellulose and graphene oxide are used as raw materials to prepare silicon carbide nanowires enhanced gallium indium liquid metal composite graphene oxide ultralight electromagnetic absorption aerogel, and ultrasonic treatment, refrigeration and vacuum lyophilization technology are used to form a porous structure to optimize impedance matching and mechanical properties.

Benefits of technology

The prepared ultralight electromagnetic absorption aerogel has low density, excellent electromagnetic absorption performance and mechanical strength, with a reflection loss between -55.50dB and -26.60dB, and an effective absorption bandwidth of 1.2-4.24GHz. It is suitable for aerospace, electronic equipment protection and communication base stations, and solves the problems of high density and poor absorption effect of existing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248411A_ABST
    Figure CN120248411A_ABST
Patent Text Reader

Abstract

The invention discloses a manufacturing method of silicon carbide nanowire reinforced gallium indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel, and belongs to the technical field of wave-absorbing composite material manufacturing, and the manufacturing method comprises the steps of silicon carbide nanowire dispersion liquid preparation, liquid metal dispersion liquid preparation, composite hydrogel preparation and post-treatment. The preparation of the silicon carbide nanowire dispersion liquid comprises the following steps: adding silicon carbide nanowires into dimethyl sulfoxide, and carrying out ultrasonic treatment to obtain a SiCnw / DMSO dispersion liquid; the preparation of the liquid metal dispersion liquid comprises the following steps: adding gallium and indium liquid metal into dimethyl sulfoxide, then adding sodium alginate, and carrying out ultrasonic crushing treatment to obtain an SA / LM / DMSO solution. By reasonably designing the material composition and the preparation process, the material is ultra-light and has excellent electromagnetic wave absorption capacity, so that the requirement of the electromagnetic absorption field on a high-performance material is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of manufacturing microwave absorbing composite materials, and particularly relates to a manufacturing method of a silicon carbide nanowire reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel. Background Art

[0002] With the rapid development of modern electronic technology, the problems of electromagnetic wave radiation and interference have become increasingly serious, and the demand for high-performance electromagnetic absorption materials is becoming more and more urgent. Traditional electromagnetic absorption materials often have problems such as high density, narrow absorption bandwidth, and unsatisfactory absorption effect. In the fields of aerospace, miniaturization of electronic devices, and military stealth, there is an urgent need to develop a material that has both ultra-light characteristics and excellent electromagnetic absorption performance. Silicon carbide nanowires have advantages such as high hardness, high melting point, and good chemical stability, and have the potential to enhance the strength of materials; gallium-indium liquid metal has excellent conductivity and can effectively dissipate electromagnetic waves; graphene oxide has a unique two-dimensional structure and excellent electrical properties, which can adjust the impedance matching of materials. However, the research on the composite preparation of these three materials into an ultra-light electromagnetic absorption aerogel still needs to be further explored. How to optimize the proportion of each component and the preparation process to achieve synergistic effects is the current challenge.

[0003] Gallium-indium liquid metal has excellent conductivity, which makes it have great potential in electromagnetic wave absorption. When electromagnetic waves act on liquid metal, its free electrons can move directionally under the action of the electromagnetic field, thereby generating an induced current, and then converting the electromagnetic wave energy into heat energy and other forms of energy loss. In addition, the fluidity of liquid metal enables it to better adapt to different application scenarios, such as having potential application value in electromagnetic shielding and absorption in flexible electronic devices. However, the surface tension of gallium-indium liquid metal is relatively large, and it is easy to agglomerate, which to a certain extent affects its dispersion and performance in composite materials.

[0004] Chinese Patent CN119144283A discloses a liquid metal-manganese oxide-MXene microwave absorbing phase change composite particle, its preparation method and application. The composite particle consists of a liquid metal core, a manganese oxide intermediate shell layer, and an MXene outer coating layer. The liquid metal can be selected from elemental gallium, gallium-indium alloy, etc.; the manganese oxide can be selected from manganese dioxide, etc.; the MXene can be selected from titanium carbide MXene, etc., and also contains a small amount of surfactant. The composite particles prepared in Example 1 were mixed with paraffin at a mass ratio of 1:1 to make a coaxial ring sample for testing. The minimum reflection loss was -53.22 dB, the maximum effective absorption bandwidth was 2.25 GHz, and the matching thickness was 1.56 mm. The composite particles prepared in Example 3 were mixed with paraffin at a mass ratio of 1:1 to make a coaxial ring sample for testing. The minimum reflection loss was -54.87 dB, the maximum effective absorption bandwidth was 4.03 GHz, and the matching thickness was 1.35 mm. Compared with the double-layer core-shell structure composite particles in the comparative example, the microwave absorption performance was better. The phase change latent heat of the composite particles prepared in Examples 1-5 was 29.8-32.9 J / g, and they had the ability to absorb heat and lower the temperature during phase change. However, due to the composite of metal oxides, the density of this material is relatively high and cannot meet the requirement of light weight.

[0005] Chinese Patent CN118837337A discloses a metasurface for surface-enhanced electromagnetic wave absorption based on liquid metal, its preparation method, application and sensor. The metasurface consists of a substrate, a buffer layer, a periodic grating layer, a metal layer, and a liquid metal layer. The liquid metal layer material contains gallium, indium, tin and their alloys. The grating structure has a specific height, width and period range, and the electromagnetic field enhancement is significant. The electric field intensity is enhanced by about 800 times, which is 26 times that of the existing metasurface. The enhanced region is concentrated in the side wall and the top gap between the grating structure and the liquid metal layer, increasing the effective sensing area. However, its application in the field of electromagnetic wave absorption has not been verified yet.

[0006] Generally speaking, the patent research on applying liquid metal with excellent properties to the field of electromagnetic wave absorption is still in its infancy. For the ultra-light electromagnetic absorption aerogel prepared by the composite of silicon carbide nanowires, gallium-indium liquid metal and graphene oxide, it is difficult to combine the advantages of the three materials with the current technology, resulting in poor synergistic effect. Summary of the Invention

[0007] Aiming at the deficiencies of the existing technology, the present invention provides a manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel. By reasonably designing the material composition and preparation process, the material is ultra-light and has excellent electromagnetic wave absorption ability to meet the requirements of high-performance materials in the field of electromagnetic absorption.

[0008] To solve the above technical problems, the technical solutions adopted by the present invention are as follows: A manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel, using silicon carbide nanowires, gallium-indium liquid metal, sodium alginate, polyvinyl alcohol, sodium carboxymethyl cellulose, and graphene oxide as raw materials, and obtaining a composite aerogel with unique structures and properties through a specific manufacturing method.

[0009] A manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel, comprising: preparing a silicon carbide nanowire dispersion, preparing a liquid metal dispersion, preparing a composite hydrogel, and post-treatment; For the preparation of the silicon carbide nanowire dispersion, silicon carbide nanowires are added to dimethyl sulfoxide and subjected to ultrasonic treatment to obtain a SiCnw / DMSO dispersion; In the preparation of the silicon carbide nanowire dispersion, the mass ratio of silicon carbide nanowires to dimethyl sulfoxide is 0.05 - 0.1:20 - 240; Preferably, the mass ratio of silicon carbide nanowires to dimethyl sulfoxide is 0.1:20; The ultrasonic treatment is carried out in an ultrasonic cleaner; The power of the ultrasonic treatment is 150 - 250 W, and the time is 10 - 20 min; Preferably, the power of the ultrasonic treatment is 200 W, and the time is 15 min; The purity of the used dimethyl sulfoxide is ≥99.9%; For the preparation of the liquid metal dispersion, gallium-indium liquid metal is added to dimethyl sulfoxide, and then sodium alginate is added, followed by ultrasonic fragmentation treatment to obtain a SA / LM / DMSO solution; In the preparation of the liquid metal dispersion, the mass ratio of gallium-indium liquid metal to dimethyl sulfoxide is 1:16 - 80; Preferably, the mass ratio of gallium-indium liquid metal to dimethyl sulfoxide is 1:80; The mass ratio of gallium-indium liquid metal to sodium alginate is 1:2 - 4; Preferably, the mass ratio of gallium-indium liquid metal to sodium alginate is 1:2; The ultrasonic fragmentation treatment is carried out in an ultrasonic cell disruptor; The power of the ultrasonic fragmentation treatment is 300 - 600 W, and the time is 20 - 30 min; Preferably, the power of the ultrasonic fragmentation treatment is 300 W, and the time is 30 min; The melting point of the gallium-indium liquid metal is ≥16°C; Preferably, the melting point of the gallium-indium liquid metal is 16°C; The purity of the sodium alginate is ≥99%; To prepare the composite hydrogel, mix the SD dispersion and the SA@LM solution, then add polyvinyl alcohol, sodium carboxymethyl cellulose, and graphene oxide dispersion, and stir to obtain the composite hydrogel; In the preparation of the composite hydrogel, the mass ratio of the SD dispersion to the SA@LM solution is 5:8 - 12; Preferably, the mass ratio of the SD dispersion to the SA@LM solution is 5:10; The mass ratio of the SD dispersion to polyvinyl alcohol is 5:1 - 3; Preferably, the mass ratio of the SD dispersion to polyvinyl alcohol is 5:2; The mass ratio of the SD dispersion to sodium carboxymethyl cellulose is 5:1 - 2; Preferably, the mass ratio of the SD dispersion to sodium carboxymethyl cellulose is 5:1; The mass ratio of the SD dispersion to the graphene oxide dispersion is 5:0.5 - 4; Preferably, the mass ratio of the SD dispersion to the graphene oxide dispersion is 5:1.5; The stirring is magnetic stirring; The rotation speed of the stirring is 400 - 600 rpm, and the time is 30 - 60 min; Preferably, the rotation speed of the stirring is 500 rpm, and the time is 60 min; The purity of the polyvinyl alcohol ≥ 99%; The molecular weight of the polyvinyl alcohol is 31000 - 50000, and the alcoholysis degree is 87 - 89%; The purity of the sodium carboxymethyl cellulose ≥ 99%; In the graphene oxide dispersion, the mass fraction of graphene oxide is 0.8 - 1.2%, and the sheet diameter of graphene oxide is 100 - 500 nm; For the post - treatment, subject the composite hydrogel to ultrasonic treatment and freezing treatment in sequence, and then perform vacuum freeze - drying treatment to obtain the ultra - light electromagnetic wave - absorbing composite aerogel; In the post - treatment, the ultrasonic treatment is carried out in an ultrasonic cleaner; The power of the ultrasonic treatment is 200 - 300 W, and the time is 1 - 5 min; Preferably, the power of the ultrasonic treatment is 300 W, and the time is 3 min; The temperature of the freezing treatment is - 40°C to - 50°C, and the time is 24 - 48 h.

[0010] Preferably, the temperature of the freezing treatment is - 50°C, and the time is 48 h; The temperature of the vacuum freeze - drying treatment is - 40°C to - 50°C, and the time ≥ 48 h; Preferably, the temperature of the vacuum freeze-drying treatment is -50°C, and the time is 48 h.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel of the present invention. The manufactured ultra-light electromagnetic absorption aerogel has the characteristic of low density, and its volume density can be as low as 0.4936 - 0.7732 g / cm 3 ; (2) The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel of the present invention. The manufactured ultra-light electromagnetic absorption aerogel has excellent electromagnetic absorption performance. When the thickness is 1.6 - 5.0 mm and the test frequency is 2 - 18 GHz, the reflection loss range is from -55.50 dB to -26.60 dB, and the effective absorption bandwidth is 1.2 - 4.24 GHz; (3) The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel of the present invention uses components such as sodium alginate, polyvinyl alcohol, graphene oxide, and sodium carboxymethylcellulose to jointly construct the framework structure of the aerogel, improving its stability and mechanical properties, and at the same time endowing the aerogel with certain flexibility and processability, so as to ensure that the manufactured aerogel has certain mechanical strength and flexibility and can adapt to different usage environments and processing requirements. Compared with traditional electromagnetic absorption materials, the manufacturing method of the aerogel of the present invention is simple, has a low cost, can be mass-produced, and has broad application prospects. For example, in the fields of aerospace, electronic equipment protection, communication base stations, etc., it can effectively solve problems such as electromagnetic interference and electromagnetic radiation; (4) The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel of the present invention composites silicon carbide nanowires, gallium-indium liquid metal, and graphene oxide, giving full play to the advantages of the three materials and achieving a synergistic effect. By regulating the introduction amount of graphene oxide to optimize the impedance matching of the aerogel, using the high electrical conductivity of gallium-indium liquid metal to enhance the electromagnetic wave loss, and using silicon carbide nanowires to adjust the impedance matching and enhance the matrix strength, thereby overcoming the problems of single material or poor synergistic effect in existing patents, and thus preparing an ultra-light and excellent electromagnetic wave absorption capacity aerogel material, filling the gap in this field. Description of the Drawings

[0012] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0013] Figure 1 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 1; Figure 2 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 2; Figure 3 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 3; Figure 4 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 4; Figure 5 Scanning electron microscope images of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Examples 1-4; In the figure, Figure 5 a- Figure 5 c are the scanning electron microscope images of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 1; Figure 5 d- Figure 5 f are the scanning electron microscope images of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 2; Figure 5 g- Figure 5 i are the scanning electron microscope images of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 3; Figure 5 j- Figure 5 l are the scanning electron microscope images of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 4; Figure 6 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 5; Figure 7 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Example 6; Figure 8 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel fabricated in Comparative Example 1; Figure 93D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel manufactured for Comparative Example 2; Figure 10 3D schematic diagram of the electromagnetic wave absorption performance of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel manufactured for Comparative Example 3. Detailed implementation manners

[0014] The various exemplary implementation manners of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, characteristics, and implementation schemes of the present invention.

[0015] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention pertains. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In case of conflict with any incorporated document, the content of this specification shall prevail.

[0016] Without departing from the scope or spirit of the present invention, various improvements and changes can be made to the specific implementation manners of the present invention specification, which are obvious to those skilled in the art. Other implementation manners obtained from the present invention specification are obvious to those skilled in the art. The present invention specification and examples are only exemplary.

[0017] The "parts" in the embodiments of the present invention refer to parts by weight unless otherwise specified.

[0018] Normal temperature in the embodiments of the present invention refers to 25 ± 2 °C.

[0019] The technical solutions of the present invention will be further described in detail below through specific examples, but the protection scope of the present invention is not limited thereto.

[0020] Example 1 A manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel, specifically as follows: 1. Prepare a silicon carbide nanowire dispersion: Weigh 0.1 g of silicon carbide nanowires (SiCnw) and add it to 20 g of dimethyl sulfoxide (DMSO). Put it into an ultrasonic cleaner and perform ultrasonic dispersion treatment for 15 min under the condition of an ultrasonic power of 200 W to obtain a SiCnw / DMSO (SD) dispersion; The purity of the dimethyl sulfoxide is 99.9%.

[0021] 2. Preparation of liquid metal dispersion: Weigh 1 g of gallium-indium liquid metal (LM) and add it to 80 g of dimethyl sulfoxide. Then add 2 g of sodium alginate (SA), and put the mixture into an ultrasonic cell disruptor. Under the condition of an ultrasonic power of 300 W, perform ultrasonic disruption treatment for 30 min to obtain an SA / LM / DMSO (SA@LM) solution in which small LM particles are dispersed. The purity of the sodium alginate is 99.5%. The melting point of the gallium-indium liquid metal is 16 °C.

[0022] Compared with an ultrasonic cleaner, the ultrasonic cell disruptor not only has a strong dispersion effect but also can break large liquid metal particles into small liquid metal particles.

[0023] 3. Preparation of composite hydrogel: Mix 5 g of SD dispersion and 10 g of SA@LM solution, then add 2 g of polyvinyl alcohol (PVA), 1 g of sodium carboxymethyl cellulose, and 0.5 g of graphene oxide (GO) dispersion, and magnetically stir at a speed of 500 r / min on a magnetic stirrer for 60 min to obtain a composite hydrogel. The purity of the polyvinyl alcohol is 99.2%, the molecular weight is 31,000 - 50,000, and the degree of alcoholysis is 87 - 89%. The purity of the sodium carboxymethyl cellulose is 99.3%. In the graphene oxide (GO) dispersion, the mass fraction of graphene oxide (GO) is 1%, and the sheet diameter of graphene oxide (GO) is 100 - 500 nm.

[0024] Polyvinyl alcohol and sodium carboxymethyl cellulose can play a role in crosslinking to form a gel, and sodium alginate, polyvinyl alcohol, and sodium carboxymethyl cellulose can form a network structure. The sodium alginate molecular chain contains a large number of hydrophilic groups and can strongly interact with water molecules; the polyvinyl alcohol molecular chain contains more hydroxyl groups and can form hydrogen bonds with polar groups of other components; sodium carboxymethyl cellulose has groups such as carboxyl groups, and the interaction between these groups enables the three components to entangle and interweave with each other during magnetic stirring to form a stable three-dimensional network structure, thus constituting the hydrogel.

[0025] 4. Post-treatment: Put the composite hydrogel into an ultrasonic cleaner and perform ultrasonic treatment for 3 min under the condition of an ultrasonic power of 300 W. Then put it into the cold trap of a freeze dryer and freeze at -50 °C for 24 h. Finally, perform vacuum freeze-drying treatment to obtain an ultra-light electromagnetic wave absorption composite aerogel. The temperature of the vacuum freeze-drying treatment is -50 °C, and the time is 48 h.

[0026] The purpose of the freezing treatment is to ensure the structural stability of the hydrogel.

[0027] Using the coaxial method of a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this embodiment is shown in Figure 1 , from Figure 1 it can be seen that the reflection loss RL of the ultra-light electromagnetic wave absorption composite aerogel prepared in this embodiment min value is -26.60 dB (14.72 GHz), and the effective absorption bandwidth EAB max is 4.24 GHz, and the thickness is 1.6 mm. Using the Archimedes drainage method, the volume density of the ultra-light electromagnetic wave absorption composite aerogel prepared in this embodiment is 0.4936 g / cm 3 .

[0028] Example 2 A manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel. On the basis of the manufacturing method of Example 1, in the step 3 of preparing the composite hydrogel, the dosage of the graphene oxide (GO) dispersion is changed to 1.0 g.

[0029] Using the coaxial method of a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this embodiment is shown in Figure 2 , from Figure 2 it can be seen that the reflection loss RL of the ultra-light electromagnetic wave absorption composite aerogel prepared in this embodiment min value is -47.11 dB (9.68 GHz), and the effective absorption bandwidth EAB max is 3.1 GHz, and the thickness is 3.3 mm; using the Archimedes drainage method to measure its volume density is 0.524 g / cm 3 .

[0030] Example 3 A manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel. On the basis of the manufacturing method of Example 1, in the step 3 of preparing the composite hydrogel and composite aerogel, the dosage of the graphene oxide (GO) dispersion is changed to 1.5 g.

[0031] Using the coaxial method of a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this embodiment is shown in Figure 3, from Figure 3 It can be seen that the reflection loss RL of the ultra-light electromagnetic wave absorbing composite aerogel prepared in this example min value is -55.50 dB (9.36 GHz), and the effective absorption bandwidth EAB max is 3.26 GHz, and the thickness is 3.0 mm; the volume density is measured by the Archimedes drainage method to be 0.5544 g / cm 3 .

[0032] Example 4 A manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic wave absorbing aerogel. On the basis of the manufacturing method of Example 1, in the step of preparing the composite hydrogel and the composite aerogel in Step 3, the dosage of the graphene oxide dispersion liquid is changed to 2.0 g.

[0033] Using the coaxial method of a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave absorbing material is 15% of the total mass of the test wave absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorbing composite aerogel manufactured in this example is shown in Figure 4 , from Figure 4 It can be seen that the reflection loss RL of the ultra-light electromagnetic wave absorbing composite aerogel prepared in this example min value is -38.22 dB (14.72 GHz), and the effective absorption bandwidth EAB max is 2.79 GHz, and the thickness is 2.4 mm; the volume density is measured by the Archimedes drainage method to be 0.5848 g / cm 3 .

[0034] The silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic wave absorbing aerogels manufactured in Examples 1-4 were respectively analyzed by scanning electron microscopy, and the obtained scanning electron microscope images are shown in Figure 5 , from Figure 5 It can be seen that the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic wave absorbing aerogels manufactured in Examples 1-4 all show a relatively obvious porous structure, indicating that when the addition amounts of the graphene oxide dispersion liquid are 0.5, 1.0, 1.5, and 2.0 g, aerogels with obvious porous structures can be obtained. Moreover, in the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic wave absorbing aerogels manufactured in Examples 1-4, the liquid metal particles are all dispersed in a spherical shape on the matrix, and the silicon carbide nanowires are bridged between the holes. After further comparison, it is found that in Example 3, that is, when the graphene oxide dispersion liquid is 1.5 g, the porous structure of the prepared silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic wave absorbing aerogel is more regular, and the distribution of the liquid metal particles is more obviously uniform.

[0035] Example 5 A manufacturing method of silicon carbide nanowire reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel. On the basis of the manufacturing method of Example 1, in the step of preparing the liquid metal dispersion liquid in the second step, the dosage of gallium-indium liquid metal is changed to 4.0 g.

[0036] Using the coaxial method of a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this example is shown in Figure 6 , from Figure 6 It can be seen that the reflection loss RL min value of the ultra-light electromagnetic wave absorption composite aerogel prepared in this example is -37.47 dB (12.24 GHz), and the effective absorption bandwidth EAB max is 1.2 GHz, and the thickness is 2.3 mm; the volume density is measured to be 0.7732 g / cm 3 .

[0037] Example 6 A manufacturing method of silicon carbide nanowire reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel. On the basis of the manufacturing method of Example 1, in the step of preparing the silicon carbide nanowire dispersion liquid in the first step, the dosage of the silicon carbide nanowire is changed to 0.05 g.

[0038] Using the coaxial method of a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this example is shown in Figure 7 , from Figure 7 It can be seen that the reflection loss RL min value of the ultra-light electromagnetic wave absorption composite aerogel prepared in this example is -40.7 dB (17.2 GHz), and the effective absorption bandwidth EAB max is 2.48 GHz, and the thickness is 5.0 mm; the volume density is measured to be 0.5413 g / cm 3 .

[0039] Comparative Example 1 A manufacturing method of silicon carbide nanowire reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel. On the basis of the manufacturing method of Example 1, in the step of preparing the composite hydrogel and composite aerogel in the third step, the addition of the reduced graphene oxide dispersion liquid is omitted.

[0040] Using the coaxial method with a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this embodiment is shown in Figure 8 , from Figure 8 it can be seen that the reflection loss RL min value of the ultra-light electromagnetic wave absorption composite aerogel prepared in this embodiment is -22.97 dB (12.24 GHz), and the effective absorption bandwidth EAB max is 2.16 GHz, and the thickness is 5.9 mm; the volume density is measured to be 0.4432 g / cm 3 .

[0041] Comparative Example 2 A manufacturing method of a silicon carbide nanowire-reinforced gallium indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel. On the basis of the manufacturing method of Example 1, the addition of sodium alginate is omitted in the second step of the liquid metal dispersion liquid step.

[0042] Using the coaxial method with a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this embodiment is shown in Figure 9 , from Figure 9 it can be seen that the reflection loss RL min value of the ultra-light electromagnetic wave absorption composite aerogel prepared in this embodiment is -14.97 dB (14.56 GHz), and the effective absorption bandwidth EAB max is 3.2 GHz, and the thickness is 1.1 mm; the volume density is measured to be 0.5471 g / cm 3 .

[0043] Comparative Example 3 A manufacturing method of a silicon carbide nanowire-reinforced gallium indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel. On the basis of the manufacturing method of Example 1, the addition of sodium carboxymethylcellulose is omitted in the third step of the preparation of the composite hydrogel and the composite aerogel step.

[0044] Using the coaxial method with a vector network analyzer (detection standard GJB5239-2004), when the addition amount of the wave-absorbing material is 15% of the total mass of the test wave-absorbing ring and the test frequency is 2-18 GHz, the 3D schematic diagram of the electromagnetic wave absorption performance of the ultra-light electromagnetic wave absorption composite aerogel manufactured in this embodiment is shown in Figure 10 , from Figure 10It can be seen that the reflection loss RL min value of the ultra-light electromagnetic wave absorption composite aerogel prepared in this embodiment is -20.97 dB (11.68 GHz), and the effective absorption bandwidth EAB max is 3.2 GHz, and the thickness is 2.0 mm; the volume density is measured by the Archimedes drainage method to be 0.5324 g / cm 3 .

[0045] By comparing the examples and comparative examples, it can be seen that the reasonable control of the parameters and composition ratios of each step in the preparation method of the present invention has a key impact on the performance of the finally prepared ultra-light electromagnetic absorption aerogel. In practical applications, these parameters can be further optimized according to specific requirements to obtain an electromagnetic absorption aerogel material with more excellent performance.

Claims

1. A manufacturing method of a silicon carbide nanowire-reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel, characterized in that, Including: Preparing a silicon carbide nanowire dispersion, preparing a liquid metal dispersion, preparing a composite hydrogel, and post-treatment.

2. The manufacturing method of the silicon carbide nanowire reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel according to claim 1, characterized in that, For the preparation of the silicon carbide nanowire dispersion, silicon carbide nanowires are added to dimethyl sulfoxide and subjected to ultrasonic treatment to obtain a SiCnw / DMSO dispersion.

3. The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel according to claim 2, characterized in that, In the preparation of the silicon carbide nanowire dispersion, the mass ratio of silicon carbide nanowires to dimethyl sulfoxide is 0.05 - 0.1:20 - 240; The ultrasonic treatment is carried out in an ultrasonic cleaner; The power of the ultrasonic treatment is 150 - 250 W, and the time is 10 - 20 min; The purity of the used dimethyl sulfoxide is ≥99.9%.

4. The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel according to claim 1, characterized in that, For the preparation of the liquid metal dispersion, gallium-indium liquid metal is added to dimethyl sulfoxide, and then sodium alginate is added, followed by ultrasonic fragmentation treatment to obtain a SA / LM / DMSO solution.

5. The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel according to claim 4, characterized in that, In the preparation of the liquid metal dispersion, the mass ratio of gallium-indium liquid metal to dimethyl sulfoxide is 1:16 - 80; The mass ratio of gallium-indium liquid metal to sodium alginate is 1:2 - 4; The ultrasonic fragmentation treatment is carried out in an ultrasonic cell disruptor; The power of the ultrasonic fragmentation treatment is 300 - 600 W, and the time is 20 - 30 min; The melting point of the gallium-indium liquid metal is ≥16°C; The purity of the sodium alginate is ≥99%.

6. The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel according to claim 1, characterized in that, For the preparation of the composite hydrogel, the SD dispersion and the SA@LM solution are mixed, and then polyvinyl alcohol, sodium carboxymethyl cellulose, and graphene oxide dispersion are added and stirred to obtain a composite hydrogel.

7. The manufacturing method of the silicon carbide nanowire reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel according to claim 6, characterized in that, In the preparation of the composite hydrogel, the mass ratio of the SD dispersion to the SA@LM solution is 5:8 - 12; The mass ratio of the SD dispersion to polyvinyl alcohol is 5:1 - 3; The mass ratio of the SD dispersion to sodium carboxymethyl cellulose is 5:1 - 2; The mass ratio of the SD dispersion to the graphene oxide dispersion is 5:0.5 - 4.

8. The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite graphene oxide ultra-light electromagnetic absorption aerogel according to claim 6, characterized in that, In the preparation of the composite hydrogel, the stirring is magnetic stirring; The rotation speed of the stirring is 400 - 600 rpm, and the time is 30 - 60 min; The purity of the polyvinyl alcohol is ≥99%; The molecular weight of the polyvinyl alcohol is 31000 - 50000, and the degree of alcoholysis is 87 - 89%; The purity of the sodium carboxymethyl cellulose is ≥99%; In the graphene oxide dispersion, the mass fraction of graphene oxide is 0.8 - 1.2%, and the sheet diameter of graphene oxide is 100 - 500 nm.

9. The manufacturing method of the silicon carbide nanowire reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel according to claim 1, characterized in that, For the post-treatment, the composite hydrogel is successively subjected to ultrasonic treatment and freezing treatment, and then vacuum freeze-drying treatment to obtain an ultra-light electromagnetic wave absorption composite aerogel.

10. The manufacturing method of the silicon carbide nanowire-reinforced gallium-indium liquid metal composite reduced graphene oxide ultra-light electromagnetic absorption aerogel according to claim 9, characterized in that, In the post-treatment, the ultrasonic treatment is carried out in an ultrasonic cleaner; The power of the ultrasonic treatment is 200 - 300 W, and the time is 1 - 5 min; The temperature of the freezing treatment is -40°C to -50°C, and the time is 24 - 48 h; The temperature of the vacuum freeze-drying treatment is -40°C to -50°C, and the time is ≥48 h.

Citation Information

Patent Citations

  • Surface-enhanced electromagnetic wave absorption metasurface based on liquid metal, preparation method, application and sensor

    CN118837337A

  • Liquid metal-manganese oxide-MXene wave-absorbing phase-change composite particle as well as preparation method and application thereof

    CN119144283A